2017
DOI: 10.9790/6737-04015460
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Prescription for Non-Communicable Diseases: Practices of Healthcare Professionals in Hospital Setting, Ethiopia.

Abstract: Introduction: Regular physical activity ( PA) plays an important role in the primary and secondary prevention of several chronic diseases, e.g., cardiovascular disease, diabetes, cancer, hypertension, obesity, depression and osteoporosis (WHO 2010, ACSM 2009

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
31
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(46 citation statements)
references
References 17 publications
(16 reference statements)
12
31
3
Order By: Relevance
“…Therefore, the descriptive survey was deemed the best strategy to fulfill the objectives of this study. Several studies on exercise counselling behavior have found the design robust [4,16,19]. The study was not expected to measure changes in exercise counselling behavior at different points in time, further logistical and time issues also influenced the design choice.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the descriptive survey was deemed the best strategy to fulfill the objectives of this study. Several studies on exercise counselling behavior have found the design robust [4,16,19]. The study was not expected to measure changes in exercise counselling behavior at different points in time, further logistical and time issues also influenced the design choice.…”
Section: Methodsmentioning
confidence: 99%
“…The healthcare setting has been recognized as an appropriate and promising venue for counseling and prescribing physical activity to increase the activity index of the population [1,2,3,4,5]. When done adequately, Healthcare Professionals' initiated physical activity (PA) counseling is moderately effective, resulting in short-term (12 months) improvements in patients' physical activity (PA) levels [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations